HUBUNGAN KECINTAAN MAHASISWA PADA MATEMATIKA DAN KECINTAANNYA PADA IPA - Sudarto, Sudarto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine whether the students' love of Mathematics is related to their love of the Science. This type of research is correlational. Respondents in this study were the PGSD FIP UNM Campus VI Bone students who took the Basic Science Concepts course in the even semester of the 2024/2025 academic year, in amount of 28 people. The data collection instrument used was a questionnaire sheet. The data analysis used was inferential analysis. Results: the data was not normally distributed and was not homogeneous, the Spearman correlation coefficient value = 0.546, and the sig. value in the Spearman correlation test = 0.003 <0.05 so that H1 was accepted and Ho was rejected. Conclusion: there is a significant correlation between the students' love of Mathematics and their love of Science and the level of the correlation is in the moderate category.